Retracted: Organic Carbon Pools in the Subsea Permafrost Domain Since the Last Glacial Maximum - Cuicui Mu; Tingjun Zhang; Benjamin W. Abbott; Kang Wang; Shemin Ge; Sayedeh Sara Sayedi; Chengyan Fan; Xiaoqing Peng (Geophysical Research Letters)
Abstract Sea level rise after the Last Glacial Maximum inundated several million square kilometers of Arctic permafrost, while estimates of organic carbon (OC) quantity and vulnerability to mineralization are exceedingly uncertain. We compiled geophysical measurements from Arctic continental shelves to estimate current subsea permafrost OC stocks. We found that marine transgression since the Last Glacial Maximum inundated approximately 3.92×106 km2 of permafrost, which contained 1,460±1,010 Pg OC in the top 25 m of sediment. We estimated that current subsea permafrost underlies an area of 2.30×106 km2 and contains 860±590 Pg OC, not including methane hydrates. Most of the ~600 Pg of OC that thawed after the marine transgression is still present on the continental shelves. Although our estimates of subsea OC storage remain highly uncertain due to the sparse and uneven distribution of data, they suggest that current estimates of subsea OC substantially underestimate a major component of the global carbon cycle.